Calcium phosphate-based organic–inorganic hybrid nanocarriers with pH-responsive on/off switch for photodynamic therapy. (14th March 2016) - Nomoto, Takahiro; Fukushima, Shigeto; Kumagai, Michiaki; Miyazaki, Kozo; Inoue, Aki; Mi, Peng; Maeda, Yoshinori; Toh, Kazuko; Matsumoto, Yu; Morimoto, Yuji; Kishimura, Akihiro; Nishiyama, Nobuhiro; et al.
Abstract : Organic–inorganic hybrid nanocarriers permit efficient photodynamic therapy with reduced damage to normal tissues. Abstract : Photodynamic therapy (PDT) is a promising treatment modality for malignant tumors in a light-selective manner. To improve the PDT efficacy, numerous kinds of nanocarriers have been developed to deliver photosensitizers (PSs) selectively into the tumor through leaky tumor-associated vasculature. However, the corresponding prolonged retention of the nanocarrier in the bloodstream may lead to unfavorable photochemical damage to normal tissues such as skin. Here, we report an organic–inorganic hybrid nanocarrier with a pH-responsive on/off switch of PDT efficacy. This hybrid nanocarrier is constructed by hydrothermal synthesis after simple mixing of calcium/phosphate ions, chlorin e6 (amphiphilic low molecular weight PS), and poly(ethylene glycol)- b -poly(aspartic acid) (PEG-PAsp) copolymers in an aqueous solution. The hybrid nanocarrier possesses a calcium phosphate (CaP) core encapsulating the PSs, which is surrounded by a PEG shielding layer. Under physiological conditions (pH 7.4), the nanocarrier suppressed the photochemical activity of PS by lowering the access of oxygen molecules to the incorporated PS, while PDT efficacy was restored in a pH-responsive manner because of the dissolution of CaP and eventual recovery of access between the oxygen and the PS. Owing to this switch, the nanocarrier reduced the photochemical damage in the bloodstream, while it induced effective PDT efficacy inside the tumor cell in response to the acidic conditions of the endo-/lysosomes.